2021
DOI: 10.1101/gad.344739.120
|View full text |Cite
|
Sign up to set email alerts
|

Esc2 orchestrates substrate-specific sumoylation by acting as a SUMO E2 cofactor in genome maintenance

Abstract: SUMO modification regulates diverse cellular processes by targeting hundreds of proteins. However, the limited number of sumoylation enzymes raises the question of how such a large number of substrates are efficiently modified. Specifically, how genome maintenance factors are dynamically sumoylated at DNA replication and repair sites to modulate their functions is poorly understood. Here, we demonstrate a role for the conserved yeast Esc2 protein in this process by acting as a SUMO E2 cofactor. Esc2 is require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 51 publications
5
17
0
Order By: Relevance
“…Given that other SUMO ligases bind to SUMO to support SUMO transfer to substrates, the apparent lack of SUMO binding by Nse2 suggests that Nse5 may substitute for it during specific sumoylation events. Interestingly, we recently found that the Esc2 protein acts as another cofactor that helps Nse2-mediated sumoylation of the STR complex and Pol2 (48). It is thus possible that Nse2 may collaborate with different cofactors to efficiently sumoylate distinct substrates, and that the Smc5/6 complex may act as a "composite SUMO ligase."…”
Section: Discussionmentioning
confidence: 99%
“…Given that other SUMO ligases bind to SUMO to support SUMO transfer to substrates, the apparent lack of SUMO binding by Nse2 suggests that Nse5 may substitute for it during specific sumoylation events. Interestingly, we recently found that the Esc2 protein acts as another cofactor that helps Nse2-mediated sumoylation of the STR complex and Pol2 (48). It is thus possible that Nse2 may collaborate with different cofactors to efficiently sumoylate distinct substrates, and that the Smc5/6 complex may act as a "composite SUMO ligase."…”
Section: Discussionmentioning
confidence: 99%
“…We have previously established an in vitro sumoylation system that can robustly sumoylate Sgs1 when the purified STR complex is incubated with purified sumoylation enzymes (Fig. S1A) (18). As seen for other sumoylation reactions, the addition of SUMO E1, SUMO E2, and SUMO in the presence of ATP are sufficient to support basal level of Sgs1 sumoylation, since the SUMO E2 can transfer SUMO to substrates upon its activation by the SUMO E1 at the consumption of ATP (14,18,22).…”
Section: Hj-dna Promotes In Vitro Sgs1 Sumoylationmentioning
confidence: 97%
“…S1A) (18). As seen for other sumoylation reactions, the addition of SUMO E1, SUMO E2, and SUMO in the presence of ATP are sufficient to support basal level of Sgs1 sumoylation, since the SUMO E2 can transfer SUMO to substrates upon its activation by the SUMO E1 at the consumption of ATP (14,18,22). For simplicity, this reaction system is referred to as basal sumoylation reaction hereafter.…”
Section: Hj-dna Promotes In Vitro Sgs1 Sumoylationmentioning
confidence: 99%
See 2 more Smart Citations